Individualistic rest interval prescription strategies for post-activation performance enancement - Vitangcol, Chris Yan Isaac S. 2000-; Papa, Emmanuel Liberato V. (Quezon City College of Human Kinetics, University of the Philippines, 2023)
Post-Activation Performance Enhancement, also known as PAPE, is the effect wherein athletic performance characteristics are improved acutely after performing a certain conditioning activity. Given the large number of variables involved in PAPE, the manner in which the phenomenon occurs varies across different athletes and protocols, making PAPE individualistic in nature. This study specifically aims to investigate the effectiveness of PAPE rest-interval protocols that can be efficiently prescribed to different athletes while catering to individual differences. Seven (n=7) recreational athletes with 6 months of strength training experience were tested on their response to fixed rest intervals (FRI), self-selected rest intervals (SSRI), and heart rate percentage-based rest intervals (HRPRI) during a PAPE protocol of one set of hex-bar deadlifts as conditioning activity to improve countermovement jump (CMJ) height. Mean CMJ Height increased using all rest interval prescription strategies (FRI 1.57 ± 3.79 cm, SSRI at 0.67 ± 3.69 cm, HRPRI at 0.12 ± 2.69.), but none showed any significant effects. Individual response to each rest interval prescription strategy also showed no consistent trend, confirming the individualistic nature of PAPE.
Vita
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Athletic ability -- Testing; Physical education and training